1925 Ind. Acts 497, § 9 - (:unkn) unknown (My University, 1925)
Prohibited the sale, delivery, or otherwise transfer of a pistol or revolver to a person who he or she has reasonable cause believe is either not a citizen or is a felon. Violatos fined not less than one hundred dollars, or imprisoned not more than one year, or both.
Keywords: TRANSFER - DANGEROUS PERSONS